If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Tanx + -1cotx = 0 Solving anxT + -1cotx = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'cotx' to each side of the equation. anxT + -1cotx + cotx = 0 + cotx Combine like terms: -1cotx + cotx = 0 anxT + 0 = 0 + cotx anxT = 0 + cotx Remove the zero: anxT = cotx Divide each side by 'nxT'. a = cn-1otT-1 Simplifying a = cn-1otT-1
| 22=-3+5u | | 2(7p+8)+6(2p+8)= | | 10-5x-10x+4= | | 4c+30=4c+20 | | c/6+2=-1 | | 2x+1=11x-28 | | 5(3-x)-2(6-5x)=33 | | 7(2)-6(-1)= | | 7(-5)-6(-3)= | | (3x+1)+(x+12)= | | 12-2j=4 | | 49x^2+101x=-67 | | -16=-4u+2(u-5) | | 7(7)-6(5)= | | 49x^2+101x+67=0 | | 7(-4)-6(0)= | | 5(3c-2)=40-2c | | 8+41nx=3 | | -33=-7(2)-3 | | b-2.25=1 | | 3(-4x-4)=5+1x | | 9(3)+2(-7)= | | 9(0)+2(-8)= | | 2y+(y-3)+3=7y-(2y+4) | | 5x+17=4(3x+1) | | 145=-u+220 | | 9(4)+2(-5)= | | =1.2 | | 49-w=232 | | 3a+5b+11b-4b+2a-6= | | x+8y^3=0 | | 9y-(5y-4)=10y-(3y+2) |